Case Report: Primary Pleural Angiosarcoma in a Patient With Klippel-Trenaunay Syndrome - Xu, Jing; Liu, Mengyao; Yuan, Hongtu; Liu, Zengjun; Zhu, Dongyuan (Frontiers in Genetics, 2022)
Klippel-Trenaunay syndrome (KTS) was demonstrated as a mosaic activating PIK3CA mutations related overgrowth syndrome. We present the first case of primary pleural angiosarcoma in a 17-year-old woman with a history of KTS. The combined targeted DNA and RNA sequencing revealed an activating mutation in PIK3CA in the tumor tissue. Our case suggested an association and perhaps a causal link between the two different PIK3CA-related genetic diseases.